"Figure 4, Peyote": Comics and Graphic Narrative in Anarchist Cookbooks, 1971-Present. Issue 3 (2nd July 2020) - Sarat-St. Peter, Hilary A.; St. Peter, Austin L.
ABSTRACT: Journalists, politicians, and law enforcement professionals have linked anarchist cookbooks to various crimes including bank robberies, hijackings, terrorist attacks, and mass shootings. By braiding comics scholarship with tactical technical communication (TTC), this article asks how anarchist cookbooks deploy comics techniques, formal features, and affordances to convey subversive tactics to audiences. We identify visual-verbal tactics that recur throughout anarchist cookbooks, identify comics elements associated with these tactics, and suggest implications for research and practice.